An Internet of Things (IoT)-based Microclimate Parameter Measurement Tool (Temperature, Humidity, and Sunlight Intensity) for Coastal Areas - Zarkasi, Ahmad; Nurhanafi, Kholis; Syahrir, Syahrir (Lambung Mangkurat University Press, 2024)
Climate parameters such as temperature, humidity, and solar light intensity can affect various things in the environment and its components such as vegetation, animals, and humans. In this research, an internet of things (IoT)-based climate parameter measurement tool has been created. The use of IoT systems offers flexibility and ease of access for observers to conduct monitoring. The designed measuring instrument has been tested and compared with a standardized measuring instrument, namely the Mastech MS6300 Environment Multitester. The test results show accuracy values of 97.1%, 95.1%, and 87.2% for temperature, humidity, and sunlight intensity measurements, respectively. The results of the measuring instrument design are implemented in coastal areas (beaches). From the results obtained, the three parameters measured tend to be stable in the morning, afternoon, and evening. Meanwhile, during the afternoon the measured climate parameters are quite fluctuating. In general, the designed measuring instrument has been able to work well and is feasible to be implemented directly.